QUALITY OF LIFE IN PATIENTS WITH HYPERTENSION INPUBLIC HEALTH CENTER SIPATANA GORONTALO CITY USING WHOQOL-Breff QUESTIONNAIRE - Fadli Husain (LP2M Universitas Bina Mandiri Gorontalo, 2019)
WHO (2011) notes that one billion people in the world suffer from hypertension and cause nearly 8 million deaths each year worldwide and nearly 1.5 million people each year in Southeast Asia. Basic Health Research (Riskesdas) in 2013 revealed the incidence of hypertension in Indonesia Reached around 25.8%. This study aims to Determine what factors are related to the quality of life of Hypertensive Patients as measured using the WHOQOL-BREF questionnaire. This research was conducted in the working region of Sipatana Health Center, Gorontalo City with the research method used was descriptive method with cross-sectional design. The research measuring instrument uses the World Health Organization Quality of Life (WHOQOL) -Bref Questionnaire, questionnaire consisting of 26 questions and is divided into four domains items, namely the domain of physical, psychological, social and environmental health quality and conducted by interviewing Patients who are being Examined health at the Sipatana Health Center. The description of the factors related to the quality of life of Hypertensive Patients at the Sipatana Health Center is Described as follows: Education Level Factors, based on the results of the study show that respondents with low education growing niche to have a poor quality of life as much as 66%. Occupational Factor. In this study, the majority of Hypertensive Patients who did not work / work did not have a poor quality of life, as many as 30 respondents (60%). Then the Joint Living Factor, based on the Chi-square statistical test, P = 0:15 Obtained a value indicating that there was no significant relationship between Hypertensive Patients with the main family living and quality of life. Finally.